Penerapan hukum waris islam: Analisis prinsip, tantangan, dan peran mediasi dalam penyelesaian sengketa di pengadilan agama - Burhanuddin, Muhammad (Maliki Interdisciplinary Journal, 2025)
Islamic inheritance law is an essential part of family law that aims to ensure justice in the distribution of an individual’s estate. The concept of faraidh lies at the core of Islamic inheritance law, providing a fair distribution guideline based on kinship, gender, and family responsibilities. However, its implementation in society faces various challenges influenced by social, cultural, economic, political, and religious factors. This study analyzes the fundamental principles of Islamic inheritance law, the factors affecting its application, and the effectiveness of mediation in resolving inheritance disputes in religious courts. The findings indicate that low legal literacy, cultural influences, and the lack of harmonization between Islamic law and positive law are the primary obstacles. Mediation in religious courts has proven effective but heavily depends on the mediator’s competence and the parties’ understanding. This study concludes that to enhance the application of Islamic inheritance law, sustained legal education, strengthening the role of religious courts, and adapting the law to modern challenges are necessary. These steps are expected to realize justice in inheritance distribution in accordance with Islamic principles